The cage-free egg sector: perspectives of Indian poultry producers - Rokade, Jaydip; Champati, Abhijeet; Sonale, Nagesh; Wadajkar, Prasad; Madheshwaran, Monika; Bhaisare, Darshana; Tiwari, Ashok Kumar (Frontiers in Veterinary Science, 2024)
India is ranked as the 2nd largest egg producer in the world. Despite the prevalence of backyard poultryies (free range), a majority of the commercial egg-laying hens in the country are still housed in battery cages. There is a global shift towards cage-free eggs, due to regulations and increased demand from conscious consumers and food corporations. However, there are very few commercial cage-free facilities in India to meet this demand. The aim of this study was to undertake a needs-assessment survey of Indian egg producers on cage-free production, and understand what support is needed to build the capacities of the cage-free egg production sector to develop it into a viable and sustainable alternative to battery cage eggs. The results showed that nearly all producers agreed on the need for additional support in shifting to, and operating in, the cage-free sector. This included support in the form of financial assistance, technical training, and promotion of the cage-free sector. The results of this study highlight the pressing need for government and private support, in the absence of which cage-free producers are compelled to compete with battery cage poultry producers on prices, which will result in increased losses and failure of the sector, since they have not yet achieved economies of scale.Animal welfare, cage-free eggs, poultry, chickens, hens, eggs, farmers, India 5. If an egg farmer decided to use a cage-free system, would they need more support in the establishment or maintenance of the farm than is currently available? (Yes/No) 6. What support would they need? (Open-ended) 7. Who should offer that support? (Open-ended) 8. What are the main operational challenges in running your cage-free farm? (Open-ended